INCONSISTENCIES IN ICSID AWARDS ON DISPUTES RELATED TO MFN AND UMBRELLA CLAUSE - Herliana Herliana (Fakultas Hukum, Universitas Diponegoro, 2021)
Investment arbitration has been acclaimed as an important part of Foreign Direct Investment (FDI) movement around the globe because it provides a neutral and trustable forum for settling investment dispute. However, many argue that investment arbitration often becomes advocates of foreign investors and neglect the developing country’s interests as the host of investment. This paper aims at studying the investment arbitration awards rendered by International Center for Settlement of Investment Dispute (ICSID) tribunals launched against developing countries. The question is whether and to what extent those awards have equally observed the interests of foreign investors and host states of investments. To answer the questions, this paper employs case study method and use publicly available ICSID cases. This research shows that some ICSID tribunals have inconsistent reasoning which led to contradictory decisions. Apparently, as some cases indicate ICSID tribunals gave more weight to the need to protect foreign investors rather than host countries’ development interests. As a consequence, inconsistency and ambiguity have led to uncertainty and unpredictability of the forum. This is not only disadvantaged the parties due to inability to foresee the likely outcome of the disputes but also endanger the ICSID tribunals’ credibility as neutral and reliable forum.